PERAN EKONOMI ONLINE SOCIAL CROWDFUNDING PLATFORM SAAT PANDEMI COVID-19 - Muhammad Nur Fadillah; Taufiq qurrachan (JURNAL MITRA MANAJEMEN, 2020)
AbstractThe corona virus or corona virus disease 2019 (Covid-19) has made the global economy contract, including Indonesia's domestic economy. The global economy is certain to slow down, a determination from the WHO which mentions the Corona outbreak as a pandemic. Singapore and South Korea are even experiencing an economic recession as a result of their domestic economic growth which has continued to decline due to the prolonged pandemic. In Indonesia, the government is trying to make various efforts to reduce the impact of the Corona virus on industry, MSMEs and society by conducting social distancing, work from home (WFH) and social assistance from both the government and the community through the Social Crowdfunding Platform that can help small and medium-sized communities maintaining the level of consumption and business activities in an effort to survive amid the current pandemic pressure. Keywords: Covid-19 Pandemic; Online Social Crowdfunding Platform; Public Consumption